2003
DOI: 10.1152/japplphysiol.00060.2003
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in acceleration during voluntary contractions lead to greater impairment of movement accuracy in old adults

Abstract: Christou, Evangelos A., Minoru Shinohara, and Roger M. Enoka. Fluctuations in acceleration during voluntary contractions lead to greater impairment of movement accuracy in old adults. J Appl Physiol 95: 373-384, 2003. First published March 21, 2003 10.1152/japplphysiol.00060. 2003.-The purpose of the study was to assess the effect of movement velocity on the relation between fluctuations in acceleration and the ability to achieve a target velocity during voluntary contractions performed by young (29.5 Ϯ 4.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 45 publications
(75 reference statements)
3
74
2
1
Order By: Relevance
“…5 and 6). Finally, both force release and lengthening contractions exhibit greater force variability than force increase and shortening contractions (Burnett et al 2000;Christou and Carlton 2002;Christou et al 2003;. In summary, the unique neural muscle activation during force release may reflect an altered strategy to control the motor neuron pool and force output, which may be similar to the one described for lengthening contractions.…”
Section: Phase and Force Variabilitymentioning
confidence: 84%
“…5 and 6). Finally, both force release and lengthening contractions exhibit greater force variability than force increase and shortening contractions (Burnett et al 2000;Christou and Carlton 2002;Christou et al 2003;. In summary, the unique neural muscle activation during force release may reflect an altered strategy to control the motor neuron pool and force output, which may be similar to the one described for lengthening contractions.…”
Section: Phase and Force Variabilitymentioning
confidence: 84%
“…When fluctuations in motor performance were evaluated by acceleration measured by an accelerometer attached to a limb, previous studies reported results in contrast to the observed changes in displacement as mentioned above. Previous findings obtained from the first dorsal interosseus muscle indicated that the SD of acceleration is larger during eccentric contractions compared with during concentric contractions 4,11,15,17) . Theoretically, acceleration is obtained by double differentiation of the displacement, and differentiation would exaggerate higher frequency bands in the source signal.…”
Section: Mechanical Characteristics Of Fluctuations In Motor Performancementioning
confidence: 85%
“…Here, stability parameters not only provide information regarding the noise present in the motor task performance, but also explicitly quantify the performance of the dynamic error correction. On the other hand, variability during specific tasks results from noise present in the motor task and in the environment [56][57][58]. In addition, variability will increase at a given noise level when error corrections are less effective.…”
Section: The Assessment Of Gait Stabilitymentioning
confidence: 99%